Numerical Simulation of Hydrogen Discharge in a Partially Enclosed Space. (2015) - Beard, Thomas; Bragin, Maxim; Malalasekera, Weeratunge; Ibrahim, Salah S.
Abstract: This paper presents the results of the numerical simulation of hydrogen discharge and dispersion in a partially enclosed space. The dispersion of hydrogen is seen as a prerequisite for combustion simulations of hydrogen. This work is a validation of an initial model and is the starting point of future work into the simulation of combustion of hydrogen within a garage. It is being performed as part of the Engineering Safe and Compact Hydrogen Energy Reserve (ESCHER) project which is working towards a home installation for hydrogen production to refuel a hydrogen vehicle overnight. The project proposes to make hydrogen via electrolysis during off-peak hours and then compressing it using a metal hydride compressor to a suitable level for the refuelling process. Using metal hydride compressor allows minimising the amount of hydrogen that is stored in the refuelling cabinet. As there are no current guidelines for hydrogen storage indoors in non-industrial sites in the UK, the safety aspects need to be examined very finely.